Odpowiedzi

Najlepsza Odpowiedź!
2010-02-13T20:09:02+01:00
Z proporcji :
9x-6=3x²-36
-3x²+9x+30=0 |/3 (dla uproszczenia rachunków
-x²+3x+10=0
a=-1 b=3 c=10
Δ=b²-4ac
Δ=9-(-4*10)=9+40=49 (Δ>0 więc rozwiązaniem są dwa pierwiastki x1 i x2)
√Δ=7
x1= -b-√Δ/2a
x1=-3-7/-2=-10/-2=5
x2=-b+√Δ/-2
x2=-3+7/-2=4/-2=-2

C! ;D
1 5 1
2010-02-13T20:12:53+01:00
3/(x² - 12) = 3/(3x - 2)
3(3x - 2) = 3(x² - 12)
9x - 6 = 3x² - 36
3x² - 9x - 36 + 6 = 0
3x² - 9x - 30 = 0
3(x² - 3x - 10) = 0
ponieważ 3 nie równa się 0 to x² - 3x - 10 musi się równać 0
x² - 3x - 10 = 0
Δ = 9 + 40
Δ = 49
√Δ = 7
x1 = 3 - 7/2 = -4/2 = -2
x2 = 3 + 7/2 = 10/2 = 5
odp C ( - 2 , 5 )
1 5 1